2011
DOI: 10.1002/jmri.22610
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertension correlates with splenic stiffness as measured with MR elastography

Abstract: Purpose To investigate the correlation between MRE assessed spleen stiffness and direct portal vein pressure gradient (D-HVPG) measurements in a large animal model of portal hypertension. Materials and Methods Cholestatic liver disease was established in adult canines by common bile duct ligation. A spin echo based EPI MRE sequence was used to acquire 3-D/3-axis abdominal MRE data at baseline, four weeks, and eight weeks. Liver biopsies, blood samples, and D-HVPG measurements were obtained simultaneously. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
73
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 26 publications
9
73
2
1
Order By: Relevance
“…Similar statistically significant differences were found for φ, which was higher in the spleen (0.607 ± 0.152) than in the liver (0.407 ± 0.044, p = 0.0008), again with a higher intrasplenic heterogeneity (SD = 0.204 ± 0.034 [liver] vs. 0.282 ± 0.076 [spleen], p = 0.0084). Similar to previous studies [24,33], we found a significant correlation between |G * | of the liver and spleen (p = 0.046), while φ was not correlated in the two organs, as has been reported in [14].…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Similar statistically significant differences were found for φ, which was higher in the spleen (0.607 ± 0.152) than in the liver (0.407 ± 0.044, p = 0.0008), again with a higher intrasplenic heterogeneity (SD = 0.204 ± 0.034 [liver] vs. 0.282 ± 0.076 [spleen], p = 0.0084). Similar to previous studies [24,33], we found a significant correlation between |G * | of the liver and spleen (p = 0.046), while φ was not correlated in the two organs, as has been reported in [14].…”
supporting
confidence: 91%
“…We use this enhanced elastodynamic information to produce mechanical parameter maps which display details of the abdomen including the liver and the spleen with fewer artifacts than previous methods. This methodological improvement is intended to provide the methodological background for a precise mechanical characterization of abdominal tissue in different clinical applications such as the assessment of lesions, staging of heterogeneous hepatic fibrosis, or detection of a vascular pressure imbalance, which may influence the elasticity ratio between the liver and spleen [24].…”
mentioning
confidence: 99%
“…MR elastography is increasingly being used clinically as a noninvasive method to stage hepatic fibrosis (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). However, MR elastography studies in patients with homogeneous HBV infection or direct comparative studies between HBV and HCV are rare (26)(27)(28)(29).…”
Section: Patientsmentioning
confidence: 99%
“…It is more frequently observed in patients with viral cirrhosis and PBC than in patients with alcoholic cirrhosis. The usefulness of splenic stiffness measurements obtained using MR elastography for detecting significant portal hypertension has recently been tested [85]. Along with splenomegaly, Gamna-Gandy bodies are usually found in the spleen of cirrhotic patients on gradient-echo MRI.…”
Section: Hemodynamic Changesmentioning
confidence: 99%